Ultrastructural studies of developing goat oocytes in-vitro - Abdullah, Ramli; Yusoff, M.; Rajikin, M.H. (1994)
The structure and distribution of organelles within developing goat oocytes at various stages of incubation were studied. In oocytes with 5 or more layers of cumulus cells, at 0 h of incubation, the zona pellucida had developed although zonation was not evident. Lipid bodies were present but no mitochondria were observed. At 20 h, the zona pellucida had differentiated into thicker and thinner regions. Clusters of membrane-bound electron-transparent bodies were present in the perivitelline space. The mitochondria were fully developed, distributed evenly and usually in close proximity with dilated endoplasmic reticula. Cortical granules were distributed at the periphery. At 40 h of incubation, a number of mitochondria was hooded. In oocytes of 2 to 4 layers of cumulus cells at 0 h, the zona pellucida was penetrated by cumulus cell processes, and the mitochondria were not well developed. However, in 20-h incubated oocytes, fully developed mitochondria, many of which were hooded, could be observed. Clusters of membrane-bound electron-transparent bodies were also observed, while cortical granules were at the periphery. In cumulus-free oocytes, zonation within the zona pellucida was indistinct. Very few vesicles and lipid bodies were observed. At 20 h, mitochondria were sparsely distributed and were not well developed and lacked cristae. At 40 h, the zona pellucida was less compact, and the membrane-bound electron-transparent bodies were less numerous compared with those of the other groups. Endoplasmic reticula were not dilated, and cortical granules were few and had no definite pattern of distribution.